(untitled) - Cha, Victor D. (Stanford, Calif., 1999)
Alignment Despite Antagonism is a carefully researched treatment of the highs and lows of US-Japan-South Korea trilateral policy coordination - one of the most difficult yet important relationships of US security interests in Asia. It merits reading by both scholars and parctitioners of East Asian security.